Crop Production under Stressful Conditions Application of Cutting-edge Science and Technology in Developing Countries (Springer Singapore, 2018)
This book presents field studies on crop production in developing countries such as Vietnam, Kenya, Namibia, Colombia, Afghanistan and Sudan. Further, it examines the achievements of SATREPS, a development assistance program sponsored by the Japanese government that promotes international joint research to address these global issues. In this context, multidisciplinary research teams consisting of breeders, physiologists, soil scientists, agronomists, and other scientists related to agricultural development worked together to tackle the challenges involved in enhancing the capacity of crop production in the respective regions. In addition to presenting novel scientific findings, this book highlights practical field studies that verify the effectiveness of the scientific findings in actual environments. The achievements will help to improve crop production worldwide, and the lessons learnt will be useful in re-designing strategies to address global issues in crop production, particularly in developing regions. Lastly, the outcomes discussed will be useful to policymakers and professionals engaged in crop production and food security in developing countries, as well as researchers and students. .